2011
DOI: 10.1021/jp108900v
|View full text |Cite
|
Sign up to set email alerts
|

Topological and Experimental Approach to the Pressure−Temperature−Composition Phase Diagram of the Binary Enantiomer System d- and l-Camphor

Abstract: In 1981, Jacques, Collet, and Wilen already put forward the idea to use pressure to influence equilibria in binary enantiomer systems in analogy with temperature (Jacques et al. Enantiomers, Racemates and Resolutions; John Wiley & Sons: New York, 1981). Whereas temperature is used routinely to study phase equilibria, pressure is an all but forgotten parameter. This is therefore possibly the first paper on the influence of pressure on a binary enantiomer system: d- and l-camphor. The study consists of two parts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 21 publications
2
10
0
Order By: Relevance
“…This means that inside sealed DSC capsules, equilibrium already exists between the solid phase and the vapor phase. If the solid melts, three phases will exist in equilibrium inside the capsule, making the melting point effectively a triple point 13–15. The same is valid for the solid–solid transition, wherein at the transition point, both solids have to be in equilibrium with the vapor pressure.…”
Section: Resultsmentioning
confidence: 96%
“…This means that inside sealed DSC capsules, equilibrium already exists between the solid phase and the vapor phase. If the solid melts, three phases will exist in equilibrium inside the capsule, making the melting point effectively a triple point 13–15. The same is valid for the solid–solid transition, wherein at the transition point, both solids have to be in equilibrium with the vapor pressure.…”
Section: Resultsmentioning
confidence: 96%
“…To calculate the eutectic temperature, the measured values for the enthalpy and temperature of fusion were used as mentioned in the Results section to maintain consistency with the values measured at higher pressures. For the pressure dependence of the transition temperature, the fit to the melting equilibrium of the pure enantiomer is used together with the melting entropy determined at ordinary pressure (57.8 J K –1 mol –1 ), which is assumed constant within the pressure range under consideration. , …”
Section: Discussionmentioning
confidence: 99%
“…The fluctuations in melting point and enthalpy may be due to the relatively high vapor pressure of ibuprofen. Camphor, another compound with a high vapor pressure, exhibits large fluctuations too in its melting enthalpy. , That ibuprofen’s different crystal habits represent one and the same crystal structure has been convincingly demonstrated by Rasenack et al and has been confirmed by Lee et al…”
Section: Introductionmentioning
confidence: 90%
“…2(b)]. To find out such stability relationships between the solid phases, the topological temperature-pressure (P-T) phase diagram must be calculated [44][45][46][47][48][49][50]. A topological P-T phase diagram accounts for the phase relationships between all the polymorphs and the vapor and liquid phases and it is a consequence of the basis of thermodynamics established by Gibbs.…”
Section: Discussionmentioning
confidence: 99%